O estágio curricular supervisionado (ecs) em cursos de graduação em Psicologia: avaliação sobre a implementação da política - Santos, Jociane Marthendal Oliveira (Universidade Federal de São Carlos, 2020)
The objective of this research was to analyze the process of implementing the policy and changes in supervised curricular internships (ECS) in undergraduate courses in Psychology after Law no. 11,788 / 2008 from the point of view of coordinators and supervisors of internship of higher education institutions in the private, confessional and public spheres. It is a qualitative research in the light of the policy cycle from the perspective of Stephen Ball according to the following procedural axes: a) review of specialized literature and documentary analysis b) data collection through semi-structured interviews in four institutions of higher education (one public, two private / community and one confessional) totaling eight subjects (four teachers and four coordinators) and c) a qualitative approach in the understanding and treatment of unidentified data to maintain confidentiality. The results showed that not all Psychology courses surveyed sought to adapt to the guidelines brought by the National Curriculum Guidelines and those who modified their curricula did so after 8 years of the Law n. 11,788 / 2008 - known as the “Internship Law”. From the institutional feedback, it was realized that the concepts and objectives of the internship are strongly linked to the world of work, evidencing the influence of the world political scenario reflecting a resistance of the courses in the traditional expansion in Brazil according to the medical model, but on the other hand justified as care not to give in and scrap the training in psychology. Even so, there is a strong tendency to continue with the Minimum Curriculum proposal and to offer specific internships later in the course. The research highlighted that the ECS policies were important in providing an internship conception aiming at competences and skills to be developed and that it contemplated the area of psychology, as well as its curricular organization and the possibility of developing the current student and the graduate as an educational act , on the other hand, it was found that it is necessary to raise awareness both to this understanding and to teachers, students and granting units for internships.
The supervised curricular internship in undergraduate courses in Psychology: evaluation on the implementation of the policy
Keywords: Estágio Curricular Supervisionado.; Psicologia.; Percurso Formativo; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS